1989
DOI: 10.1364/ol.14.000116
|View full text |Cite
|
Sign up to set email alerts
|

Efficient diode-array-pumped Nd:YAG and Nd:Lu:YAG lasers

Abstract: Nd:YAG (YAG) and Nd:Lu:YAG (LYAG) are investigated as high-efficiency laser materials utilizing a diode-array side-pump geometry. We demonstrate higher laser efficiencies than previously reported for transversely pumped YAG. A YAG rod yielded an optical slope efficiency of 47.7%, while a LYAG rod yielded an optical slope efficiency of 50.3%. Increased performance of these materials is attributed to higher pump absorption and lower losses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…In recent years, Nd 3 þ -doped mixed garnets, including Nd:GdYAG, Nd:LuYAG and Nd:GdLuAG, have attracted many researchers' attention [1][2][3][4][5]. For inheriting a large number of excellent properties such as high thermal conductivity, excellent physical and chemical properties from single garnets, the mixed garnets were also used widely in solid state lasers [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, Nd 3 þ -doped mixed garnets, including Nd:GdYAG, Nd:LuYAG and Nd:GdLuAG, have attracted many researchers' attention [1][2][3][4][5]. For inheriting a large number of excellent properties such as high thermal conductivity, excellent physical and chemical properties from single garnets, the mixed garnets were also used widely in solid state lasers [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…And the broadening fluorescence line can generally improve the laser performance in Q-switched regimes. In 1989, Allik et al demonstrated the higher laser efficiency of Nd:LuYAG mixed garnet than Nd:YAG garnet [1]. By employing Nd:LuYAG garnet as laser gain medium, Di et al demonstrated stable mode-locked laser with a pulse width of 6.6 ps [4].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, much attention has been paid to the development of new materials that have better diode-pumpedlaser properties than the conventional Nd:YAG [1][2][3][4][5]. The new materials are required to have a larger absorption coefficient and longer fluorescent lifetime, as well as excellent thermal, chemical and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…, the solid solution of LuAG and YAG, combines the advantages of the two end member compounds and has broadened absorption and emission spectra with Re 3+ -doping owing to the structural disorder. Spectral broadening in mixed crystals favors diode pumping and is highly desirable as well for widely tunable operation and short pulse generation [19][20][21][22][23][24][25]. Efficient lasing of Nd 3+ -and Tm 3+ -doped LuYAG at 1 and 2 μm have already been demonstrated with either similar or even superior laser performances to that of Nd 3+ -and Tm 3+ -doped YAG [20,22], but to our knowledge, no laser report has so far been found based on Er 3+ -doped LuYAG mixed crystal at ∼ 1.6 μm.…”
Section: Introductionmentioning
confidence: 99%